The Role of Food Distribution System and Product Innovation on Availability and Affordability of Functional Food in Sukabumi District - Sudirjo, Frans; Lubis, Mitra Musika; Priyana, Yana (West Science Interdisciplinary Studies, 2024)
This study examines the role of the food distribution system and product innovation in enhancing the availability and affordability of functional foods in Sukabumi District. Using a quantitative approach, data were collected from 170 respondents through a structured questionnaire employing a Likert scale of 1 to 5. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was utilized to analyze the relationships between variables. The results reveal that the food distribution system has a strong positive effect on affordability and a moderate effect on availability, while product innovation significantly impacts both affordability and availability, with a stronger influence on the latter. The combined explanatory power for affordability and availability demonstrates the critical interplay between distribution efficiency and innovation in ensuring functional food accessibility. These findings provide actionable insights for policymakers, producers, and distributors to address logistical and innovation-related challenges, thereby promoting sustainable food systems in the region.